Penanggulangan Sinar Ultraviolet Dan Pemakaian Lensa Fotokromik Pada Pelanggan Di Optik Rindani Kota Solok - suryanta, Dolly iman (Jurnal Sains Farmasi Dan Kesehatan, 2023)
This scientific paper discusses the selection of photochromic lenses for exposure to ultraviolet light at Optik Rindani, Solok City. This research aims to find out: (1) find out how to overcome exposure to ultraviolet light at Optik Rindani, Solok City. (2) find out the choice of photoromic lenses at Optik Rindani, Solok City. This research design uses quantitative descriptive methods. The population in this study were all Pure Optik Rindani patients in Solok City with a sample of 30 respondents. Data was collected through a questionnaire, then the data was discussed in accordance with the theory proposed in the literature review. The results of this research showed that the average frequency of respondents who answered the questionnaire items with the answer "Yes" was 13 people with a percentage of 42.6% and the total average frequency of respondents who answered the questionnaire items "No '' as many as 17 people with a percentage of 57.4%. From these results, it can be said that 57.4% of respondents at Optik Rindani Kota Solok do not know how to deal with exposure to ultraviolet rays and the total average frequency of respondents who answered the questionnaire questions with the answer "Yes" was 21 people with the percentage was 71.0% and the total average frequency of respondents who answered the questionnaire items "No" was 9 people with a percentage of 29.0%. From these results, it can be said that 71.0% of respondents at Optik Rindani, Solok City chose to use photochromic lenses.